Antisocial personality, emotional intelligence and tendency of aggressive behavior among undergraduate university students in Lahore, Pakistan - Rabi, Imdad (2018)
The main purpose of this study was to explore the relationship between antisocial personality, emotional intelligence and tendency of aggressive behavior among undergraduate university students in Lahore, Pakistan. The relationship between antisocial personality, emotional intelligence and tendency of aggressive behavior has received very little attention. Thus, the current research was essential and necessary. This study was based on a quantitative approach. The respondents were 380 male and female undergraduate university students aged between 18 and 23 years. Respondents were identified using Multi-stage cluster sampling and data was collected using a set of questionnaires. The instruments used were Aggressive Behavior Questionnaire (BPAQ; Buss and Perry, 1992), Emotional Intelligence Scale (Schutte, 1998), Antisocial Personality Scale (Andershed, Kerr and Station, 2000; and Forth, Kosson and Hare, 2003). Descriptive statistics, independent sample t-test, correlation and regression analysis were conducted; while the mediating effect was estimated using bootstrap bias corrected 95% confidence interval technique. Hierarchical multiple linear regression was utilized to estimate the moderating role of gender in the relationship between antisocial personality and aggressive behavior.The results of the descriptive analysis of the level of the tendency of aggressive behavior showed that out of the 380 respondents, 27.6% (105) of the respondent were reported to have low, 56.8% (216) of the respondent were reported to have moderate level and 15.5% (59) of the respondents have a high level of tendency of aggressive behavior. The level of antisocial personality 21.6% (82) of them were reported to have low level, 48.4% (184) were reported to have moderate level and 30.0% (114) of the respondent have a high level of antisocial personality. The level of emotional intelligence revealed that 17.1% (65) have a low level, 41.6% (158) have moderate level and 41.3% (157) had a high level of emotional intelligence. The independent Samples t-test was used to identify differences in tendency of aggressive behavior, antisocial personality and emotional intelligence between gender and family system groups. The finding indicated that there was no significant difference in antisocial personality, emotional intelligence and tendency of aggressive behavior among gender. The findings indicate that students from nuclear families showed a higher tendency of aggressive behavior than those from joint families. Similarly students from nuclear family showed higher antisocial personality than those from joint families. In addition students from joint families were found to have higher emotional intelligence than students from nuclear families. Moreover, the Pearson correlation was used to determine the relationship between antisocial personality, emotional intelligence, age, number of siblings and tendency of aggressive behavior among undergraduate university students. The findings of the Pearson correlation analysis showed that there was a significant positive relationship between antisocial personality and tendency of aggressive behavior among the students. However, the finding of the Pearson correlation between emotional intelligence and tendency of aggressive behavior showed a significant negative relationship. Furthermore, the findings of the Pearson correlation between age and number of siblings and tendency of aggressive behaviour were not significant. The findings also showed that antisocial personality is the most important predictor of tendency of aggressive behavior among undergraduate university students. Multiple regression analysis was used to show that antisocial personality, emotional intelligence, and family system (nuclear) significantly contribute to the tendency of aggressive behavior among students. Testing for mediating role of emotional intelligence on the relationship between antisocial personality and tendency of aggressive behavior was conducted using bootstrapping method based on the 95% bias – corrected (BC) confidence interval (CI). The results confirmed that emotional intelligence plays a mediating role in the relationship between antisocial personality and tendency of aggressive behavior among undergraduate university students.A hierarchical multiple linear regression analysis was conducted to examine the moderating role of gender on the relationships between antisocial personality and tendency of aggressive behavior. The relationship between antisocial personality with tendency of aggressive behavior was not found to be moderated by gender. In conclusion, the findings of this study highlighted some implications, such as the theoretical implication, practical and policy implications in regard to the antisocial personality, emotional intelligence and tendency of aggressive behavior among the undergraduate university students.